APPLICATION OF MATHEMATICAL LOGIC IN SOLVING OF SOME EQUATION, INEQUALITIES, SYSTEM OF EQUATION AND INEQUALITIES IN THE COURSE OF MATHEMATICS LYCEUM - HARITON, Andrei; CALMUȚCHI, Laurențiu (Acta et Commentationes, Sciences of Education, 2019)
Elements of mathematical logic and sets theory have entered significantly in the mathematics school curriculum beginning with primary classes. The logic-set conception has contributed to more effective teaching-learning-evaluation of mathematics in gymnasium and lyceum. It is obvious that the perspective of the logic-set conception in increasing the mathematical school results is very great. This paper opens new possibilities in using the logic-set conception